Soy Phytoestrogens and Breast Cancer Chemoprevention: Molecular Mechanisms - Satih, Samir; Rabiau, Nadege; Bignon, Yves-Jean; Bernard-Gallon, Dominique J. (Current Nutrition & Food Science, 2008)
Breast cancer is an important public health problem worldwide and it represents the second leading cause of cancer-related deaths among women in most industrialized countries. Epidemiological studies suggest a much lower incidence of breast cancer in women from countries with high soy phytoestrogen consumption such as China and Japan than the Western world. Phytoestrogens are a group of plant-derived polyphenol compounds that exhibit structural and functional similarities to the human steroid hormone 17β-estradiol. Genistein and daidzein, the main soy phytoestrogens, are two estrogen-mimicking compounds which can bind to estrogen receptors and exert weak estrogenic effects. There are several possible mechanisms by which these phytochemicals may reduce the risk of breast cancer; however their precise mechanisms of action remain to be elucidated. This review will summarize the properties of genistein and daidzein as phytoestrogens, and their chemopreventive effects in breast carcinogenesis including their antioxidant properties, antiinflammatory activities as well as their antiprogression abilities, and their importance in xenobiotic metabolism. Because the use of soy phytoestrogens is increasing, it is important from a public health perspective and a mechanistic understanding to study the potential links existing between soy phytoestrogens and breast cancer prevention.
Keywords: genistein